2018
DOI: 10.20473/ijosh.v6i3.2017.381-389
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Stres Kerja Terhadap Peningkatan Tekanan Darah Pada Pekerja

Abstract: Work stress occurs when the demands of the job do not match with capabilities, resources, needs and worker discontent. One of the effects of   work stress is increased blood pressure. This study was performed to determine the effect of work stress on the increased of blood pressure in press cutting PT.X. This study is analytical study which is explain the influence work stress to increase of blood pressure. This study using  cross sectional methodology. The population of this study is people who work at press … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
1
2
0
1
Order By: Relevance
“…The results of the research are in accordance with the results of the research conducted by Kurniasari and Hidayat (2018) who showed noted in their research showed a significant relationship between occupational stress and increased blood pressure. Respondents with high working stress will experience elevated blood pressure, while those with low working stress also experience increased blood pressure in the low category (Kurniasari and Hidayat, 2018).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of the research are in accordance with the results of the research conducted by Kurniasari and Hidayat (2018) who showed noted in their research showed a significant relationship between occupational stress and increased blood pressure. Respondents with high working stress will experience elevated blood pressure, while those with low working stress also experience increased blood pressure in the low category (Kurniasari and Hidayat, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…If the stress is not managed properly then the increase in blood pressure can be patoligis/sedentary, so it will cause strokes and heart attacks (Kurniasari and Hidayat, 2018). Companies need to identify the factors that are the cause of stress in this company.…”
Section: Discussionmentioning
confidence: 99%
“…Workers with stress while working have a 5.62 times higher chance of having blood and pulse pressures. Even though those are not significant, prevention is still necessary so that when someone has fatigue, there would be proper help [5] . Blood pressure arises on the walls of the arteries as a result of cardiac activity.…”
Section: ~ 120 ~mentioning
confidence: 99%
“…Hasil uji statistik mengunakan uji Rank Spearman diperoleh nilai p sebesar 0,148 (p>0,05), maka H0 diterima sehingga tidak ada hubungan antara umur lansia dengan tekanan darah. 13…”
Section: E-issn 2721-2920unclassified